Algorithm for the Representation of Parameter Values of Electrocardiogram - Sabar Setiawidayat; Rudy Joegijantoro (Universitas Ahmad Dahlan, 2018)
Important parameters that need to be known from the results of cardiac examination using Electrocardiograph is the parameter value of PQRST amplitude peak on each lead. Peak P is associated with Atrium depolarization, QRS waves associated with ventricle depolarization and peak T associated with ventricle repolarization. The PQRST peak values on each lead to date are still manually calculated using small boxes on the ECG paper. Manual calculations lead to less accurate results and calculated waiting times. Less accuracy can lead to misdiagnosis while waiting times can result in increased disease stage. In this article we have been able to represent the values of PQRST amplitude peak and cardiogram in each cycle on each lead of the electrocardiogram. Continuous signal Electrocardiogram (ECG) examination results, in sampling at certain frequencies to obtain discrete data which is the amplitude as a function of integer numbers (N). The maximum amplitude value of each cycle is peak R. The peak time duration R to peak R (dR) is used as the time period of each cycle. A 1.5dR reversal of RN + 1 reverses the starting point of the cycle (sc) while the 0.5dR duration reversal of RN + 1 will be obtained by the end point of the cycle (ec). The maximum and minimum amplitude values between sc and peak R are peak P and peak Q respectively, while the minimum and maximum values between peak R to ec are peak Q and peak T respectively. Discrete data from Physionet MIT-BIH and bmeuwg are used as data to obtain PQRST peak electrocardiogram parameter values in each cycle.